Pengaruh Fungsi Kepemimpinan Camat terhadap Motivasi Kerja Pegawai di Kantor Camat Sipatana Kota Gorontalo - swastiani Dunggio; Mutia Kengo (Program Studi Ilmu Pemerintahan, 2025)
This study aims to analyze the influence of leadership functions, including planning, initiating, controlling, and evaluating, on employee work motivation at the Sipatana District Office in Gorontalo City. The study employed a quantitative approach with a census technique involving 31 employees. Data were collected through a questionnaire that had been tested for validity and reliability, then analyzed using path analysis with the help of SPSS. The results indicate that leadership functions significantly influence employee work motivation, both partially and simultaneously. Simultaneously, leadership functions contributed 78.3% to employee work motivation, while the remaining influence was attributed to factors outside the study. Therefore, the implementation of effective leadership functions plays a crucial role in improving employee work motivation in government environments.